Score of Fine Motor Skill in Children with Down Syndrome using Nintendo Wii - Sinaga, Puspasari; Prananta, Marietta Shanti; Fadlyana, Eddy (Althea Medical Journal, 2016)
Background: Down syndrome occurs due to an extra chromosome 21, known as Trisomy 21. In addition to delayed cognitive and speech development, children with Down syndrome may also experience delayed gross and fine motor development. Virtual Reality Therapy, such as Nintendo Wii is a computer-based technology that allows users to interact with a virtual three-dimensional scenario and the most innovative physical rehabilitation method. High scores indicate that the player has a good motor skill. This study aimed to examine the difference between the score of fine motor skill in children with and without Down syndrome.Methods: An analytic cross-sectional study was conducted from August to November 2015 to 40 children aged between 9â12 years old who came from public primary schools and special needs schools in Bandung, West Java. They were divided into 2 groups using random gender and age pairing; one group was children with Down syndrome and another other group was normal children. The childrenâ scores of Nintendo Wii game were collected three times. The collected data were statistically analyzed by Chi-Square test.Results: The proportion of children with low-grade fine motor skill in Down syndrome group was larger than those with high-grade fine motor skill. In the other hand, in normal children group, the proportion was reversed compared to Down syndrome group. There was a significant difference in score of fine motor skill between children with Down syndrome and normal children (p=0.000).Conclusions: The fine motor skill of children with Down syndrome is poorer than normal childrenâs. [AMJ.2016;3(3):371â5]Â DOI: 10.15850/amj.v3n3.882Â